2017
DOI: 10.1001/journalofethics.2017.19.11.stas2-1711
|View full text |Cite
|
Sign up to set email alerts
|

Why Aren't Our Digital Solutions Working for Everyone?

Abstract: The article explores a digital injustice that is occurring across the country: that digital solutions intended to increase health care access and quality often neglect those that need them most. It further shows that when it comes to digital innovation, health care professionals and technology companies rarely have any incentives to focus on underserved populations. Nevertheless, we argue that the technologies that are leaving these communities behind are the same ones that can best support them. The key is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…For instance, previous work showed that even the most basic functions of apps are difficult to use for diverse populations (45). Top-funded digital health companies test only 30% of their apps in people with clinical conditions (46). These factors are important because individuals with lower health literacy have worse health outcomes over time due to difficulty making informed health choices (47).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, previous work showed that even the most basic functions of apps are difficult to use for diverse populations (45). Top-funded digital health companies test only 30% of their apps in people with clinical conditions (46). These factors are important because individuals with lower health literacy have worse health outcomes over time due to difficulty making informed health choices (47).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, digital access is considered a social determinant of health, with 21 million adults in the United States lacking access to broadband internet [ 24 ]. With the transition to web-based research, we risk compounding this structural disadvantage and not realizing the potential to expand research access to increasingly diverse and underrepresented populations [ 1 ] without targeted measures to address digital access and literacy [ 21 , 25 , 26 ].…”
Section: Strategies For Remote Data Collectionmentioning
confidence: 99%
“…It is not entirely surprising that Internet connectivity, the availability of quality and upto-date equipment, and digital literacy are now considered "super-determinants of health": they indeed engage all the other determinants that directly or indirectly influence the health of individuals and communities by now being primarily accessible online (e.g., affordable housing, employment, social assistance, social and family networks, and access to care and services) (86). The crisis has also shown that the technologies used in the delivery of care and services "often neglect those that need them most" as health professionals and technology providers are rarely given the incentive to better meet needs and expectations of underserved populations in terms of digital innovation (86)(87)(88).…”
Section: Digital Divide and Equity Issuesmentioning
confidence: 99%
“…Digital technologies will shape the future of the HSSS, and possibly our societies, by driving the next generation of care and services (87). The form this transformation takes will depend on the choices made in the light of the lessons learned from the pandemic.…”
Section: Legal and Regulatorymentioning
confidence: 99%